Framework of Chinese traditional residential building decorations for the sustainability of Chinese culture in cultural and creative industries - Tianxi, Lu; Herman, Siti Sarah; Ismail, Nor Atiah (Universiti Teknologi MARA, Perak, 2025)
Culture supports the achievement of multiple sustainable development goals. Promoting the sustainability of Chinese culture could make a positive contribution to global sustainable development. Chinese traditional residential building decorations (TRBDs) are carriers of Chinese culture. This study is part of a large-scale research project exploring the relationship between Chinese traditional residential building decoration culture and the development of the cultural and creative industries (CCIs). It aims to explore the application of Chinese traditional residential building decorations for the sustainability of Chinese culture in CCIs using a systematic literature review method. This paper elucidates the latest research progress on CCIs, Chinese TRBDs, and the sustainability of Chinese culture. Subsequently, through a cross-analysis method, this paper proposes a framework for CCIs to use traditional Chinese residential building decorations to promote cultural sustainability. The framework advocates exploring the cultural genes within traditional Chinese residential building decorations to foster the synergistic effects of the economy, society, culture, and technology within CCIs. This approach is expected to promote innovation in content, technology, and culture within CCIs while bringing economic and social benefits and enhancing the protection and innovation of Chinese culture.